KINERJA SISTEM LUP TERTUTUP DENGAN PENGENDALI LINEAR QUADRATIC GAUSSIAN PADA SISTEM MASSA PEGAS - ., Predesia; ., Widowati (MATEMATIKA, 2013)
Linear Quadratic Gaussian (LQG) controller is one of the controllers used to stabilize a plant. The plant is an object that is controlled. The procedure to find this controller as follows; first, the plant is balanced so that controllability and observability Grammians is equal to square Hankel singular values diagonal matrix, then look for the controller gain and estimator gain that are solutions of Riccati equations. Next, construct a state space realization of LQG controller. To verify the performance of the obtained controller, its was applied for the spring mass system. Further, by using MATLAB program, the performance of the closed loop system with the LQG controller and the open loop system is compared. The simulation results show that the closed loop system can be stabilized in less than 10 seconds, whereas the open loop system can be stabilized in 3000 seconds. This indicate that the performance of the closed loop system with LQG controller better than the open loop system